Circulation of emerging NDM‐5‐producing Escherichia coli among humans and dogs in Egypt. (22nd December 2019) - Ramadan, Hazem; Gupta, Sushim K.; Sharma, Poonam; Ahmed, Marwa; Hiott, Lari M.; Barrett, John B.; Woodley, Tiffanie A.; Frye, Jonathan G.; Jackson, Charlene R.
Abstract: The emergence of NDM‐producing Escherichia coli has considerably threatened human and animal health worldwide. This study describes for the first time in Egypt, the draft genome sequences of emerging NDM‐5‐producing E. coli from humans and dogs, and investigates genetic relatedness between isolates from both sources. Two E. coli from human urine and seven from environmental clinical samples of dogs exhibited resistance to carbapenems and harbouring bla NDM were subjected to Illumina Miseq whole‐genome sequencing (WGS). Assembly and analysis of the reads were performed to identify resistance genes, multilocus sequence types (MLST), plasmid replicon types (Inc) and insertion sequences (IS) of the bla NDM region; core genome MLST (cgMLST) analysis was also performed. Two different NDM alleles were identified; bla NDM‐5 in E. coli HR119 from the urine of a healthy person and environmental samples of dogs, and bla NDM‐1 in E. coli HR135 from a human patient's urine. Multiple mobilizable resistance genes to different antimicrobial classes were identified except the colistin resistance gene, mcr . E. coli isolates from humans and dogs were assigned to different sequence types (STs). Using cgMLST, dog isolates clustered together with only 1–2 allellic differences; however, human E. coli showed 1, 978 different allelles compared with dog isolates. Plasmidfinder results indicated the presence of an IncX3 replicon in bla NDM‐5 ‐producing E. coli ; however, bla NDM‐1 was linked to IncCoIKP3. Notably, the NDM region (3 Kb) in all isolates from humans and dogs was highly similar with variable flanking sequences that represented different IS elements. This study reports the first emergence of NDM‐5‐producing E. coli from dogs in Egypt that shared some genetic features with human isolates and could be considered potential public health threats.